Transparent conductive oxide and preparation method thereof
By using a transparent conductive oxide film including a seed layer, a conductive layer and a protective layer in a silicon heterojunction solar cell, the problems of suede irregularity and large contact resistance caused by the wet etching process are solved, and the problem of "suede irregularity" and "maximum contact resistance" is achieved. Efficient battery performance improvement and cost reduction.
Patent Information
- Application Number
- CN202411207335.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2025-02-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
During the preparation process of existing silicon heterojunction solar cells, the wet etching process leads to poor irregularity and controllability of suede, which affects the battery performance, and the contact resistance between the nanocrystalline silicon film and the TCO film is relatively large. Limits the battery filling factor.
A transparent conductive oxide film is adopted, which includes a seed layer, a conductive layer and a protective layer. The seed layer is an indium tin oxide film or a gallium/aluminum co-doped zinc oxide film, and the conductive layer is a gallium/aluminum co-doped zinc oxide film. , the protective layer is an indium tin oxide film. The film is prepared by a sol deposition process and is subjected to annealing and secondary annealing to improve its conductivity and stability.
The method of the transparent conductive oxide film is cheap and has a fast deposition rate, which can reduce substrate damage and improve the conversion efficiency and application range of heterojunction batteries. The design of the seed layer and protective layer reduces the contact barrier, improves the battery filling factor, and enhances the film stability.
Smart Images

Figure CN119403287A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries, and in particular relates to a transparent conductive oxide and a preparation method thereof. Background Art
[0002] As energy crisis and environmental pollution become increasingly serious, people pay more attention to the research and application development of new energy. Among them, solar photovoltaic power generation technology has become a research hotspot in the field of new energy due to its cleanliness, safety and renewable nature. Among them, silicon heterojunction solar cells have become an important development direction of the current solar energy industry due to their advantages such as low preparation method temperature, high photoelectric conversion efficiency, excellent high temperature / weak light power generation and low attenuation.
[0003] Silicon heterojunction solar cells generally include a crystalline silicon substrate, a front electrode and a back electrode composed of a transparent conductive oxide (TCO) film and located on both sides of the crystalline silicon substrate, and a heterogeneous PN junction composed of amorphous silicon / crystalline silicon located between the front electrode and the back electrode. When sunlight irradiates the PN junction, the built-in electric field separates the photogenerated hole-electron pairs generated by the light, thereby forming non-equilibrium carriers and generating current. In the preparation process of silicon heterojunction solar cells, in order to minimize light reflection and improve the photoelectric conversion efficiency of the cell, a velvet surface is usually made on the surface of the crystalline silicon substrate.
[0004] At present, silicon heterojunction solar cells generally use wet etching to make a textured surface on the surface of a crystalline silicon substrate. However, the textured surface made by wet etching is not regular, resulting in serious recombination of photogenerated carriers, which affects the performance of silicon heterojunction solar cells. Moreover, the wet etching process has poor controllability during actual operation, that is, the textured surface structure of crystalline silicon substrates made by different batches of the same process is quite different. At the same time, impurities introduced during the wet etching process will also contaminate the crystalline silicon substrate, affecting the photoelectric conversion efficiency of silicon heterojunction solar cells. In order to improve the conversion efficiency of silicon heterojunction solar cells, it is necessary to form a good ohmic contact between the contact interface of amorphous silicon and TCO film. The usual method is to grow a layer of highly doped amorphous silicon film or nanocrystalline silicon film between the contact interface of amorphous silicon and TCO film. However, the amorphous silicon film or nanocrystalline silicon film grown by PECVD is usually limited in conductivity due to the limited carrier concentration of the material, and the work function between the amorphous silicon film or nanocrystalline silicon film and the TCO film does not match, resulting in a large contact resistance between the amorphous silicon film or nanocrystalline silicon film and the TCO film, which affects the final fill factor of the silicon heterojunction solar cell. On the other hand, with the development of photovoltaic application technology and information technology, the speed of depositing nanocrystalline silicon film in industrialized silicon heterojunction solar cells is very slow, which affects the production cycle of the battery and increases the preparation cost of the battery.
[0005] Transparent conductive oxide (TCO) films have been widely used in pan-optoelectronic semiconductor fields such as low-E glass, flat panel displays, light-emitting diodes, photoelectric detection, optoelectronic communications, and solar cells due to their excellent optoelectronic properties.
[0006] In heterojunction solar cell (SHJ) applications, TCO thin films have three important functions: 1. Acting as an effective collection and transmission carrier for photogenerated carriers, which requires good conductivity; 2. Acting as a surface anti-reflection window layer; 3. Acting as a surface protection layer. In addition, in addition to having the optoelectronic properties required to meet the performance of the cell, the materials and preparation costs of the TCO thin films must also be strictly controlled. Summary of the invention
[0007] In view of the above-mentioned deficiencies in the prior art, the present invention provides a transparent conductive oxide and a preparation method thereof, so as to solve the above-mentioned problems in the background technology.
[0008] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0009] A transparent conductive oxide comprises a seed layer, a conductive layer and a protective layer, wherein the seed layer comprises an indium tin oxide film or a gallium / aluminum co-doped zinc oxide film, the conductive layer is a gallium / aluminum co-doped zinc oxide film, the protective layer is an indium tin oxide film, the thickness of the indium tin oxide film in the transparent conductive oxide thin film is less than the thickness of the gallium / aluminum co-doped zinc oxide film, and the transparent conductive oxide thin film is prepared by the following preparation method, the preparation method comprising the following steps: providing a substrate; and depositing a transparent conductive oxide thin film on the substrate by a deposition process;
[0010] Step 1, obtaining a sol solution of an indium salt and a doped metal salt, wherein the viscosity of the sol solution is 21 to 25 mPa·s, the concentration of indium in the indium salt is 0.1 to 1 mol / L, the doped metal salt is at least one of a tin salt, a nickel salt and a molybdenum salt, and the molar ratio of indium to the doped metal is 0.05 to 0.15;
[0011] Step 2, immersing the film-forming medium into the sol solution, staying for 1 to 30 seconds, then pulling the medium out of the sol liquid surface at a speed of 1 to 300 cm / min, and then keeping it at 80°C to 300°C for 0.5 to 30 minutes, and cooling; wherein the process of keeping it at 80°C to 300°C for 0.5 to 30 minutes is divided into two steps of drying and heat treatment, and the pulled film-forming medium is placed at 80°C to 150°C for drying for 0.5 minutes to 15 minutes to obtain a gel film, and then the gel film is placed at 150°C to 300°C for preheating for 0.5 minutes to 15 minutes;
[0012] Step 3, repeating step 2 until the film thickness on the film-forming medium reaches a desired thickness, thereby obtaining the transparent conductive oxide thin film;
[0013] Step 4: annealing the transparent conductive oxide film at a temperature of 250° C. to 800° C. for 10 min to 3 h;
[0014] Step 5: Perform secondary annealing on the transparent conductive oxide film in a reducing atmosphere, wherein the temperature of the secondary annealing is 250° C. to 800° C. and the time is 0.5 min to 1 h; the reducing gas of the reducing atmosphere is an inert gas or a mixed gas of nitrogen and hydrogen.
[0015] Furthermore, the carrier concentration of the seed layer is >6×10 20 and the thickness is <10 nm.
[0016] Furthermore, the carrier concentration of the conductive layer is less than 2×10 20 and the thickness is greater than 40 nm.
[0017] Furthermore, the material of the transparent conductive oxide film is an indium oxide material doped with a transition metal, and the transition metal includes one or more of tin, cerium, zirconium, titanium, hafnium, zinc and manganese.
[0018] Furthermore, the carrier mobility of the transparent conductive oxide film is 100 cm2 / V·S to 170 cm2 / V·S.
[0019] A method for preparing a transparent conductive oxide comprises the following steps:
[0020] Step 1, obtaining a sol solution of an indium salt and a doped metal salt, wherein the viscosity of the sol solution is 21 to 25 mPa·s, the concentration of indium in the indium salt is 0.1 to 1 mol / L, the doped metal salt is at least one of a tin salt, a nickel salt and a molybdenum salt, and the molar ratio of indium to the doped metal is 0.05 to 0.15;
[0021] Step 2, immersing the film-forming medium into the sol solution, staying for 1 to 30 seconds, then pulling the medium out of the sol liquid surface at a speed of 1 to 300 cm / min, and then keeping it at 80°C to 300°C for 0.5 to 30 minutes, and cooling; wherein the process of keeping it at 80°C to 300°C for 0.5 to 30 minutes is divided into two steps of drying and heat treatment, and the pulled film-forming medium is placed at 80°C to 150°C for drying for 0.5 minutes to 15 minutes to obtain a gel film, and then the gel film is placed at 150°C to 300°C for preheating for 0.5 minutes to 15 minutes;
[0022] Step 3, repeating step 2 until the film thickness on the film-forming medium reaches a desired thickness, thereby obtaining the transparent conductive oxide thin film;
[0023] Step 4: annealing the transparent conductive oxide film at a temperature of 250° C. to 800° C. for 10 min to 3 h;
[0024] Step 5: Perform secondary annealing on the transparent conductive oxide film in a reducing atmosphere, wherein the temperature of the secondary annealing is 250° C. to 800° C. and the time is 0.5 min to 1 h; the reducing gas of the reducing atmosphere is an inert gas or a mixed gas of nitrogen and hydrogen.
[0025] Furthermore, the preparation steps of the sol solution of the indium salt and the doped metal salt are as follows:
[0026] Adding an indium salt to an organic solvent, and then adding a stabilizer in an equal molar ratio to the indium salt, placing the mixture at a temperature of 60° C. to 100° C., and stirring for 0.5 h to 10 h to obtain an indium salt solution;
[0027] dissolving a doped metal salt in an organic solvent to obtain a doped metal salt solution;
[0028] The indium salt solution and the doped metal salt solution are mixed, stirred at 50° C. to 150° C. for 0.5 h to 10 h, and then allowed to stand for 24 h to 48 h to obtain a sol solution of the indium salt and the doped metal salt.
[0029] Furthermore, the organic solvent is at least one of isopropanol, acetylacetone, and ethylene glycol methyl ether, and the stabilizer is diethanolamine and / or monoethanolamine.
[0030] Furthermore, the indium salt and the doping metal salt are at least one of their corresponding alkoxides, acetates, vinylacetone salts, nitrates, and chlorides.
[0031] Furthermore, the viscosity of the sol solution is 17-18 mPa·s.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] 1. The preparation method of transparent conductive oxide has the advantages of low cost and high deposition rate. It can not only prepare high-quality transparent conductive oxide films, but also reduce substrate damage, which is of great significance for improving the conversion efficiency and application scope of heterojunction batteries.
[0034] 2. The seed layer in the transparent conductive oxide film includes an indium tin oxide film or a gallium / aluminum co-doped zinc oxide film. The seed layer can reduce the contact barrier between the transparent conductive oxide film and the P-type doped amorphous silicon film and the N-type doped amorphous silicon film, thereby obtaining a lower contact resistance. At the same time, the indium tin oxide film is used as a protective layer to improve the stability of the transparent conductive oxide film, ensure the battery efficiency and reduce the battery attenuation. Among them, the conductive layer is a gallium / aluminum co-doped zinc oxide film, and the thickness of the indium tin oxide film in the transparent conductive oxide film is less than the thickness of the gallium / aluminum co-doped zinc oxide film, which can reduce the cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a schematic diagram of the structure of a transparent conductive oxide film according to an embodiment of the present application;
[0036] The reference numerals in the drawings of the specification include:
[0037] Seed layer 1, electrical layer 2, protective layer 3. DETAILED DESCRIPTION
[0038] In order to enable those skilled in the art to better understand the present invention, the technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0039] Among them, the drawings are only used for illustrative explanations, and they only represent schematic diagrams rather than actual pictures, and should not be understood as limitations on this patent; in order to better illustrate the embodiments of the present invention, some parts of the drawings may be omitted, enlarged or reduced, and do not represent the size of the actual product; for those skilled in the art, it is understandable that some well-known structures and their descriptions in the drawings may be omitted.
[0040] The same or similar numbers in the drawings of the embodiments of the present invention correspond to the same or similar parts; in the description of the present invention, it should be understood that if the terms "upper", "lower", "left", "right", "inner", "outer", etc. appear, the orientation or position relationship indicated is based on the orientation or position relationship shown in the drawings, which is only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation. Therefore, the terms describing the position relationship in the drawings are only used for illustrative purposes and cannot be understood as a limitation on this patent. For ordinary technicians in this field, the specific meanings of the above terms can be understood according to specific circumstances.
[0041] In the description of the present invention, unless otherwise clearly specified and limited, if the term "connection" or the like appears to indicate the connection relationship between components, the term should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two components or the interaction relationship between two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0042] Embodiment 1:
[0043] like Figure 1 As shown, the present invention. Specifically, a transparent conductive oxide includes a seed layer, a conductive layer and a protective layer, the seed layer includes an indium tin oxide film or a gallium / aluminum co-doped zinc oxide film, the conductive layer is a gallium / aluminum co-doped zinc oxide film, the protective layer is an indium tin oxide film, the thickness of the indium tin oxide film in the transparent conductive oxide thin film is less than the thickness of the gallium / aluminum co-doped zinc oxide film, and the transparent conductive oxide thin film is prepared by the following preparation method, which includes the following steps: providing a substrate; and depositing a transparent conductive oxide thin film on the substrate by a deposition process;
[0044] Step 1, obtaining a sol solution of an indium salt and a doped metal salt, wherein the viscosity of the sol solution is 21 to 25 mPa·s, the concentration of indium in the indium salt is 0.1 to 1 mol / L, the doped metal salt is at least one of a tin salt, a nickel salt and a molybdenum salt, and the molar ratio of indium to the doped metal is 0.05 to 0.15;
[0045] Step 2, immersing the film-forming medium into the sol solution, staying for 1 to 30 seconds, then pulling the medium out of the sol liquid surface at a speed of 1 to 300 cm / min, and then keeping it at 80°C to 300°C for 0.5 to 30 minutes, and cooling; wherein the process of keeping it at 80°C to 300°C for 0.5 to 30 minutes is divided into two steps of drying and heat treatment, and the pulled film-forming medium is placed at 80°C to 150°C for drying for 0.5 minutes to 15 minutes to obtain a gel film, and then the gel film is placed at 150°C to 300°C for preheating for 0.5 minutes to 15 minutes;
[0046] Step 3, repeating step 2 until the film thickness on the film-forming medium reaches a desired thickness, thereby obtaining the transparent conductive oxide thin film;
[0047] Step 4: annealing the transparent conductive oxide film at a temperature of 250° C. to 800° C. for 10 min to 3 h;
[0048] Step 5: Perform secondary annealing on the transparent conductive oxide film in a reducing atmosphere, wherein the temperature of the secondary annealing is 250° C. to 800° C. and the time is 0.5 min to 1 h; the reducing gas of the reducing atmosphere is an inert gas or a mixed gas of nitrogen and hydrogen.
[0049] Furthermore, the carrier concentration of the seed layer is >6×10 20 and the thickness is <10 nm.
[0050] Furthermore, the carrier concentration of the conductive layer is less than 2×10 20 and the thickness is greater than 40 nm.
[0051] Furthermore, the material of the transparent conductive oxide film is an indium oxide material doped with a transition metal, and the transition metal includes one or more of tin, cerium, zirconium, titanium, hafnium, zinc and manganese.
[0052] Furthermore, the carrier mobility of the transparent conductive oxide film is 100 cm2 / V·S to 170 cm2 / V·S.
[0053] A method for preparing a transparent conductive oxide comprises the following steps:
[0054] Step 1, obtaining a sol solution of an indium salt and a doped metal salt, wherein the viscosity of the sol solution is 21 to 25 mPa·s, the concentration of indium in the indium salt is 0.1 to 1 mol / L, the doped metal salt is at least one of a tin salt, a nickel salt and a molybdenum salt, and the molar ratio of indium to the doped metal is 0.05 to 0.15;
[0055] Step 2, immersing the film-forming medium into the sol solution, staying for 1 to 30 seconds, then pulling the medium out of the sol liquid surface at a speed of 1 to 300 cm / min, and then keeping it at 80°C to 300°C for 0.5 to 30 minutes, and cooling; wherein the process of keeping it at 80°C to 300°C for 0.5 to 30 minutes is divided into two steps of drying and heat treatment, and the pulled film-forming medium is placed at 80°C to 150°C for drying for 0.5 minutes to 15 minutes to obtain a gel film, and then the gel film is placed at 150°C to 300°C for preheating for 0.5 minutes to 15 minutes;
[0056] Step 3, repeating step 2 until the film thickness on the film-forming medium reaches a desired thickness, thereby obtaining the transparent conductive oxide thin film;
[0057] Step 4: annealing the transparent conductive oxide film at a temperature of 250° C. to 800° C. for 10 min to 3 h;
[0058] Step 5: Perform secondary annealing on the transparent conductive oxide film in a reducing atmosphere, wherein the temperature of the secondary annealing is 250° C. to 800° C. and the time is 0.5 min to 1 h; the reducing gas of the reducing atmosphere is an inert gas or a mixed gas of nitrogen and hydrogen.
[0059] Furthermore, the preparation steps of the sol solution of the indium salt and the doped metal salt are as follows:
[0060] Adding an indium salt to an organic solvent, and then adding a stabilizer in an equal molar ratio to the indium salt, placing the mixture at a temperature of 60° C. to 100° C., and stirring for 0.5 h to 10 h to obtain an indium salt solution;
[0061] dissolving a doped metal salt in an organic solvent to obtain a doped metal salt solution;
[0062] The indium salt solution and the doped metal salt solution are mixed, stirred at 50° C. to 150° C. for 0.5 h to 10 h, and then allowed to stand for 24 h to 48 h to obtain a sol solution of the indium salt and the doped metal salt.
[0063] Furthermore, the organic solvent is at least one of isopropanol, acetylacetone, and ethylene glycol methyl ether, and the stabilizer is diethanolamine and / or monoethanolamine.
[0064] Furthermore, the indium salt and the doping metal salt are at least one of their corresponding alkoxides, acetates, vinylacetone salts, nitrates, and chlorides.
[0065] Furthermore, the viscosity of the sol solution is 17-18 mPa·s.
[0066] Example 2
[0067] Dissolve indium nitrate in acetylacetone, add ethanol methyl ether in an equal molar ratio to indium nitrate, place in a 90°C water bath, stir for 1.5 hours, and form a transparent homogeneous solution A. To prepare a solution doped with Sn2+ ions, first dissolve tin nitrate in anhydrous ethanol to prepare a transparent solution B with a concentration of 0.5 mol / L. Drop solution B into solution A, control the molar ratio of Sn and In to 0.1, and add isopropanol to adjust the indium nitrate concentration of the solution to 0.5 mol / L. Then, after fully stirring at 90°C for 2 hours, a transparent homogeneous solution is formed, poured into a clean wide-mouth bottle, and allowed to stand for 24 hours to obtain a sol solution for use.
[0068] Select stainless steel foil with the specification of 80mm×80mm×0.5mm. Insert the cleaned stainless steel foil vertically into the prepared sol, let the substrate stay in the sol for 15S, so that it can reach adsorption equilibrium on the substrate, and then pull it up at a speed of 15cm / min. After each pull, dry it at 100℃ for 5min to obtain a gel film, then heat treat it at 300℃ for 1min, and repeat the above operation 10 times after cooling.
[0069] After the coating reaches the required number of times, it is sent to a rapid thermal treatment furnace and annealed at 500°C in an air atmosphere for 20 minutes. Then it is annealed at 550°C in a reducing atmosphere (flow ratio (N2:H2) 90:10), with a gas flow rate of 40mL / min, and annealed for 10 minutes to obtain a transparent conductive oxide film. Film thickness: 300nm; resistance: 2.5×10-4Ω·cm; visible light transmittance: 93%.
[0070] Example 3
[0071] Dissolve zinc acetate dihydrate (Zn(AC)2·2H2O) in isopropanol, then add diethanolamine (DEA) in an equal molar ratio to zinc acetate dihydrate, place in a 70℃ water bath, stir for 2h, and form a transparent homogeneous solution A. To prepare the Al3+ ion-doped solution, first dissolve aluminum nitrate nonahydrate (Al(NO3)3·9H2O, analytical grade) in anhydrous ethanol to prepare a transparent solution B with a concentration of 0.5mol / L. Drop solution B into solution A, control the molar ratio of Al and Zn to 0.01, and add isopropanol to adjust the zinc acetate concentration of the solution to 0.8mol / L. Then, after fully stirring at 100℃ for 3h, a transparent homogeneous solution is formed, poured into a clean wide-mouth bottle, and allowed to stand for 48h to obtain a sol solution for use.
[0072] Select an optical glass sheet with the size of 25mm×80mm×1mm. Insert the cleaned glass sheet vertically into the prepared sol, let the substrate stay in the sol for 10 seconds to allow it to reach adsorption equilibrium on the substrate, and then pull it up at a speed of 8cm / min. After each pull, dry it at 100℃ for 15min to obtain a gel film, then heat treat it at 240℃ for 1min, and repeat the above operation 20 times after cooling.
[0073] The above are only embodiments of the present invention, and the circuits, electronic components and modules involved are all prior art, which can be fully implemented by those skilled in the art. It is needless to say that the content protected by this application does not involve improvements to software and methods. The common sense such as the known specific structures and characteristics in the scheme is not described in detail here. Ordinary technicians in the relevant field know all the common technical knowledge in the technical field of the invention before the application date or priority date, can obtain all the prior art in the field, and have the ability to apply conventional experimental means before that date. Ordinary technicians in the relevant field can improve and implement this scheme in combination with their own abilities under the enlightenment given by this application. Some typical known structures or known methods should not become obstacles for ordinary technicians in the relevant field to implement this application. It should be pointed out that for those skilled in the art, without departing from the structure of the present invention, several deformations and improvements can be made, which should also be regarded as the scope of protection of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent.
Claims
1. A transparent conductive oxide, comprising a seed layer, a conductive layer and a protective layer, wherein the seed layer comprises an indium tin oxide film or a gallium / aluminum co-doped zinc oxide film, the conductive layer is a gallium / aluminum co-doped zinc oxide film, the protective layer is an indium tin oxide film, the thickness of the indium tin oxide film in the transparent conductive oxide thin film is less than the thickness of the gallium / aluminum co-doped zinc oxide film, and the invention is characterized in that: The transparent conductive oxide film is prepared by the following preparation method, which comprises the following steps: providing a substrate; and depositing the transparent conductive oxide film on the substrate by a deposition process; Step 1, obtaining a sol solution of an indium salt and a doped metal salt, wherein the viscosity of the sol solution is 21 to 25 mPa·s, the concentration of indium in the indium salt is 0.1 to 1 mol / L, the doped metal salt is at least one of a tin salt, a nickel salt and a molybdenum salt, and the molar ratio of indium to the doped metal is 0.05 to 0.15; Step 2, immersing the film-forming medium into the sol solution, staying for 1 to 30 seconds, then pulling the medium out of the sol liquid surface at a speed of 1 to 300 cm / min, and then keeping it at 80°C to 300°C for 0.5 to 30 minutes, and cooling; wherein the process of keeping it at 80°C to 300°C for 0.5 to 30 minutes is divided into two steps of drying and heat treatment, and the pulled film-forming medium is placed at 80°C to 150°C for drying for 0.5 minutes to 15 minutes to obtain a gel film, and then the gel film is placed at 150°C to 300°C for preheating for 0.5 minutes to 15 minutes; Step 3, repeating step 2 until the film thickness on the film-forming medium reaches a desired thickness, thereby obtaining the transparent conductive oxide thin film; Step 4: annealing the transparent conductive oxide film at a temperature of 250° C. to 800° C. for 10 min to 3 h; Step 5: Perform secondary annealing on the transparent conductive oxide film in a reducing atmosphere, wherein the temperature of the secondary annealing is 250° C. to 800° C. and the time is 0.5 min to 1 h; the reducing gas of the reducing atmosphere is an inert gas or a mixed gas of nitrogen and hydrogen.
2. A transparent conductive oxide according to claim 1, characterized in that: The seed layer has a carrier concentration of >6×10 20 and a thickness of <10 nm.
3. A transparent conductive oxide according to claim 1, characterized in that: The conductive layer has a carrier concentration of <2×10 20 and a thickness of >40 nm.
4. A transparent conductive oxide according to claim 1, characterized in that: The material of the transparent conductive oxide film is an indium oxide material doped with a transition metal, and the transition metal includes one or more of tin, cerium, zirconium, titanium, hafnium, zinc and manganese.
5. A transparent conductive oxide according to claim 1, characterized in that: The carrier mobility of the transparent conductive oxide film is 100cm2 / V·S to 170cm2 / V·S.
6. A method for preparing a transparent conductive oxide, characterized in that: The steps include: Step 1, obtaining a sol solution of an indium salt and a doped metal salt, wherein the viscosity of the sol solution is 21 to 25 mPa·s, the concentration of indium in the indium salt is 0.1 to 1 mol / L, the doped metal salt is at least one of a tin salt, a nickel salt and a molybdenum salt, and the molar ratio of indium to the doped metal is 0.05 to 0.15; Step 2, immersing the film-forming medium into the sol solution, staying for 1 to 30 seconds, then pulling the medium out of the sol liquid surface at a speed of 1 to 300 cm / min, and then keeping it at 80°C to 300°C for 0.5 to 30 minutes, and cooling; wherein the process of keeping it at 80°C to 300°C for 0.5 to 30 minutes is divided into two steps of drying and heat treatment, and the pulled film-forming medium is placed at 80°C to 150°C for drying for 0.5 minutes to 15 minutes to obtain a gel film, and then the gel film is placed at 150°C to 300°C for preheating for 0.5 minutes to 15 minutes; Step 3, repeating step 2 until the film thickness on the film-forming medium reaches a desired thickness, thereby obtaining the transparent conductive oxide thin film; Step 4: annealing the transparent conductive oxide film at a temperature of 250° C. to 800° C. for 10 min to 3 h; Step 5: Perform secondary annealing on the transparent conductive oxide film in a reducing atmosphere, wherein the temperature of the secondary annealing is 250° C. to 800° C. and the time is 0.5 min to 1 h; the reducing gas of the reducing atmosphere is an inert gas or a mixed gas of nitrogen and hydrogen.
7. A transparent conductive oxide according to claim 6, characterized in that: The preparation steps of the sol solution of the indium salt and the doped metal salt are as follows: Adding an indium salt to an organic solvent, and then adding a stabilizer in an equal molar ratio to the indium salt, placing the mixture at a temperature of 60° C. to 100° C., and stirring for 0.5 h to 10 h to obtain an indium salt solution; dissolving a doped metal salt in an organic solvent to obtain a doped metal salt solution; The indium salt solution and the doped metal salt solution are mixed, stirred at 50° C. to 150° C. for 0.5 h to 10 h, and then allowed to stand for 24 h to 48 h to obtain a sol solution of the indium salt and the doped metal salt.
8. A transparent conductive oxide according to claim 7, characterized in that: The organic solvent is at least one of isopropanol, acetylacetone and ethylene glycol methyl ether, and the stabilizer is diethanolamine and / or monoethanolamine.
9. A transparent conductive oxide according to claim 7, characterized in that: The indium salt and the doped metal salt are at least one of their corresponding alkoxides, acetates, vinylacetone salts, nitrates, and chlorides.
10. A transparent conductive oxide according to claim 7, characterized in that: The viscosity of the sol solution is 17-18 mPa·s.